POLA PENDIDIKAN ISLAM PADA MASA NABI MUHAMMAD SAW DI MEKAH DAN MADINAH - Leli Purnama; Lufita Sari Sitorus; Sri Belia Harahap; Tihawa (Jurnal Cahaya Madrasah, 2025)
ABSTRACT This research aims to uncover the patterns of Islamic education implementation during the early period of Prophet Muhammad (peace be upon him) in Mecca and Medina, serving as a reference for developing Islamic education aligned with Islamic values for the present and future. The development of Islamic teachings during the Prophet's time in Mecca and Medina reflects a phase of glory that demonstrates the purity of Islamic doctrine, with Prophet Muhammad (peace be upon him) as the central figure. The study focuses on the evolution of Islamic education in the Mecca and Medina periods, employing a qualitative approach through library research. In the early era encompassing pre-Islamic Arabia, the prophethood period, and the time of the companions education bore distinctive characteristics shaped by the prevailing social, cultural, and religious context. Arab culture at that time highly valued oral traditions and the transmission of knowledge via stories passed down through generations, thereby according great honor to knowledge as the primary foundation of education. Following Islam's advent, the education system became structured, centering on the teaching of the Quran and hadith. During the Prophet's era, learning initially occurred informally in mosques and community settings; it later evolved into a more systematic and organized form under the Caliphate, marked by the establishment of madrasahs and formal institutions teaching various fields of knowledge. The research reveals that prophetic Islamic education comprised two main phases: Mecca and Medina. In Mecca, it unfolded in three stages secret, open, and public proclamation. In Medina, education aimed to forge a new, unified society socially and politically, incorporating aspects of social-political and citizenship education. Thus, this study is vital for revealing prophetic educational patterns applicable today while safeguarding Islam's purity and providing a comprehensive perspective on Islamic education as the basis for communal living.